Students’ Motivation Toward Online Learning at Universitas Negeri Medan - Halimahtu Saddiah (Lembaga Pengembangan Kinerja Dosen, 2026)
Abstract. This study aims to describe students’ motivation toward online learning at Universitas Negeri Medan and to identify the underlying reasons for such motivation. The research employed a descriptive qualitative design, utilizing the ARCS (Attention, Relevance, Confidence, Satisfaction) motivational model and Expectancy-Value Theory as the theoretical frameworks. Data were collected through an online questionnaire distributed to 34 English Education students and semi-structured interviews with 5 purposively selected participants. The results indicated that all four components of the ARCS model were in the moderate category, with mean scores of 3.16 for Attention, 3.29 for Relevance, 3.20 for Confidence and 3.20 for Satisfaction. While students appreciated the flexibility and accessibility of online materials (high utility value), they frequently experienced boredom and mental fatigue due to limited social interaction and the